2021
DOI: 10.1080/13506285.2021.1915903
|View full text |Cite
|
Sign up to set email alerts
|

The malleability of attentional capture

Abstract: We suggest that consideration of trial-by-trial variations, individual differences, and training data will enrich the current framework in Luck et al. (2020). We consider whether attentional capture is modulated by trial-by-trial fluctuations of attentional state and experiences on the previous trial. We also consider whether individual differences may affect attentional capture while highlighting potential challenges in using the color-singleton task to measure individual differences. Finally, performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This variability may indicate that words capture attention more automatically for some individuals than for other individuals. The underlying causes of this variability are undoubtedly multifaceted, but we suspect that reading skill, working memory capacity, and other attention-control capabilities (e.g., the ability to minimize mind wandering; Forster & Lavie, 2014; Zhang et al, 2021) contribute to the variability reported herein.…”
Section: Discussionmentioning
confidence: 87%
“…This variability may indicate that words capture attention more automatically for some individuals than for other individuals. The underlying causes of this variability are undoubtedly multifaceted, but we suspect that reading skill, working memory capacity, and other attention-control capabilities (e.g., the ability to minimize mind wandering; Forster & Lavie, 2014; Zhang et al, 2021) contribute to the variability reported herein.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies tackled the malleability aspects of some mindfulness-related concepts. The malleability of attention (Zhang et al, 2021) is relevant for the attention segment of the mindfulness concept, while the malleability of rumination (Bessette et al, 2020) can be connected to the present-focus aspect of mindfulness. In contrast to these constructs, our focus on mindset regarding mindfulness was broader and included four already well-explored components (attention, awareness, present orientation, and acceptance) constituting mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, recent studies examined mindsets about concepts relevant to mindfulness. The malleability of attention (Zhang et al, 2021) is relevant to the attention part of the mindfulness concept, while the malleability of rumination (Bessette et al, 2020) can be connected to the present focus aspects. The malleability of attention or rumination can grasp specific features of mindfulness but cannot reflect on its multifaceted nature.…”
Section: Mindfulness Mindset Among Similar Mindset Constructs In the ...mentioning
confidence: 99%
“…We have previously argued that the effect of attentional capture is quite malleable in that it varies from trial to trial and from person to person (Zhang et al, 2021). However, research has mostly focused on uncovering the "general principles" of attentional guidance.…”
Section: What Is the Role Of Past Experience In The Effect Of Abrupt ...mentioning
confidence: 99%
“…Although this concern has been widely recognized and rigorously explored in fields like attentional control, it has only recently gained serious attention among researchers interested in attentional capture. Recent investigations into the split-half and test-retest reliability of certain attentional capture tasks have revealed that the typically used RT difference scores exhibit suboptimal reliability (Anderson & Kim, 2019;Ivanov et al, 2023;Zhang et al, 2021). To appropriately study individual differences in attentional capture, we need to pay closer attention to principles from the psychometric tradition.…”
Section: What Is the Role Of Past Experience In The Effect Of Abrupt ...mentioning
confidence: 99%